2017
DOI: 10.1001/jamafacial.2016.1180
|View full text |Cite|
|
Sign up to set email alerts
|

Yield Strength Testing in Human Cadaver Nasal Septal Cartilage and L-Strut Constructs

Abstract: IMPORTANCE To our knowledge, yield strength testing in human nasal septal cartilage has not been reported to date. An understanding of the basic mechanics of the nasal septum may help surgeons decide how much of an L-strut to preserve and how much grafting is needed. OBJECTIVES To determine the factors correlated with yield strength of the cartilaginous nasal septum and to explore the association between L-strut width and thickness in determining yield strength. DESIGN, SETTING, AND PARTICIPANTS In an anatomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The L-strut, named in reference to its shape, is the remaining intact region of the septum after submucous resection during septoplasty or graft harvesting ( Figure 1). To avoid nasal collapse, it is widely accepted that the minimum widths of the caudal and dorsal arms of the L-strut need to be 10 mm [95]. However, it has been shown that thickness of the L-strut has a greater impact on L-strut yield strength [25,95].…”
Section: 23: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The L-strut, named in reference to its shape, is the remaining intact region of the septum after submucous resection during septoplasty or graft harvesting ( Figure 1). To avoid nasal collapse, it is widely accepted that the minimum widths of the caudal and dorsal arms of the L-strut need to be 10 mm [95]. However, it has been shown that thickness of the L-strut has a greater impact on L-strut yield strength [25,95].…”
Section: 23: Mechanical Propertiesmentioning
confidence: 99%
“…To avoid nasal collapse, it is widely accepted that the minimum widths of the caudal and dorsal arms of the L-strut need to be 10 mm [95]. However, it has been shown that thickness of the L-strut has a greater impact on L-strut yield strength [25,95]. Despite its importance, thickness is rarely taken into account in L-strut mechanical strength modeling due to the complexity of accounting for both dimensions during rhinoplasty.…”
Section: 23: Mechanical Propertiesmentioning
confidence: 99%
“…Because the thickness of the septum has been shown to be greatest adjacent to the septal base and most narrow in the central portion of the septum and near the ASP, the nasal septum adjacent to the ASP is afflicted with both decreased L‐strut width as well as with a thin depth. As prior research has shown, changing the anatomical constructs of L‐struts affects its underlying strength as compared to the unaltered septa . As such, the C‐strut concept informs the surgeon, during creation of the cartilage cuts, to arc the incisions posteriorly in a curvilinear fashion, paralleling the natural caudal and dorsal arc to ensure adequate strut width and maximal cartilage harvest.…”
Section: Discussionmentioning
confidence: 99%
“…As prior research has shown, changing the anatomical constructs of L-struts affects its underlying strength as compared to the unaltered septa. 2,10,12,13 As such, the C-strut concept informs the surgeon, during creation of the cartilage cuts, to arc the incisions posteriorly in a curvilinear fashion, paralleling the natural caudal and dorsal arc to ensure adequate strut width and maximal cartilage harvest. For example, a surgeon working within the L-strut paradigm may adequately estimate the strut width from the ASP but continue a linear cartilage cut that does not adequately provide enough distance from the PCSP.…”
Section: Discussionmentioning
confidence: 99%
“…Since septal shape shows significant variability between individuals, these studies may not be representative of the general patient population [6]. Furthermore, while studies have focused on the width of the dorsal and caudal struts, Liu et al showed that thickness is a more important determinant of overall L-strut strength [15].…”
Section: Finite Elemental Analysismentioning
confidence: 99%